Development and Deployment of THEIA: A Compact Underwater Multispectral Imaging System - S. Spanos; C. Antoniou; V. Ntouskos; V. Ntouskos; A. Mallios; P. Nomikou; K. Karantzalos (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
We present THEIA, a novel underwater 3D multispectral imaging system. THEIA integrates a 4MP multispectral field array camera and a high-resolution RGB stereo camera pair in a specially built underwater housing to simultaneously capture spectral and depth information. This enables detailed spectral mapping and 3D reconstructions of underwater scenes. High resolution multispectral images are obtained via a Deep Image Prior-based demosaicing algorithm that enhances the multispectral data resolution without relying on external training. Stereo imaging provides depth cues for performing radiance correction. By suitably adapting Gaussian Splat-based 3D reconstruction methods, THEIA generates high-fidelity multispectral 3D models. Successful field trials at the Kolumbo underwater volcano validate the system’s reliability and potential for applications in marine science and beyond.